(untitled) (Research, Society and Development, 2020)
In the State of Ceará, the introduction of new species and cultivars in the agricultural scenario brings a new perspective of business in the sector, as well as new demands for the consumer market of quality exotic fruits. Thus, the aim of this work was to characterize two varieties of Pomegranate through the analysis of their physical, physical-chemical characteristics and their respective productivities. The fruits were collected in the second and third harvest of the second year of cultivation of the two varieties of Pomegranate (CV8 and CV12) in an orchard located in Tabuleiro de Russas, CE. The physical variables analyzed were fruit weight, diameter, productivity and for physico-chemical characterization, pH, soluble solids, titratable acidity and the ratio between soluble solids and titratable acidity were analyzed. Based on the results found, the CV8 variety showed the highest productivity. Using the titratable acidity parameter, the percentage found for the two varieties characterizes them as sweet fruits. And when the SS / ATT parameter was analyzed, the CV8 variety was considered to have a higher degree of sweetness. Thus, it can be inferred that the CV8 variety is characterized as having the greatest aptitude for fresh consumption.